Ferdinand Karl Piëch: A Psychobiography of a Ruthless Manager and Ingenious Engineer - Mayer, Claude-Hélène; van Niekerk, Roelf; Wannenburg, Nicola (Frontiers in Psychology, 2021)
The dark sides of personalities have gained importance during the past two decades. Psychobiography deals with the life of extraordinary individuals throughout the life span by applying selected theories to analyse specific life aspects. This study uses Theodore Millon’s (1990, 2011) personality theory to explore the life of Ferdinand Karl Piëch (1937-2019), an Austrian engineer and business executive who was the chairman of the executive board of the Volkswagen Group (1993-2002) and the chairman of the supervisory board from 2002-2015. Piëch was also known for having a complex and controversial personality. This study aims to explore the life and work of Ferdinand Karl Piëch through the lens of Millon’s personality theory. This study has four specific aims. Firstly, to provide an accurate and objective description of Piëch’s life history. Secondly, to formulate an accurate description of Piëch’s personality on the basis of existing biographical data. Thirdly, to interpret Piëch’s personality through the use of Millon’s theoretical framework and identify the personality prototypes that correspond with his personality characteristics. Fourthly, to contribute to expanding the field of “dark personality aspects” from a psychobiographical perspective, especially the personalities of extraordinary individuals. The findings suggest that although Piëch demonstrated the characteristics of three personality prototypes, the assertive-sadistic prototype is the best fit for his personality characteristics. Conclusions are drawn and recommendations for theory and practice are given.